Decontamination of Chicken Breasts Using Organic Acids and Lauricidin - Anang, Daniel Mensah (2005)
Lauricidin, lactic and oxalic acids were evaluated for their effectiveness in reducing and inhibiting the growth of predominant spoilage and pathogenic microorganisms. Chicken breasts (150 - 200 g each) of freshly slaughtered chickens were purchased from a local wet market and analysed within 2 hr. Chicken breasts were dipped in 0, 0.5, 1.0, 1.5 and 2.0% solutions of lauricidin (w!v, containing 1% lactic acid and 1% ethanol), lactic acid (v/v) or oxalic acid (w/v) for 10, 20 and 30 min, then individually packed in oxygen-permeable polyethylene bags, and stored at 4°C. Aerobic plate counts (APC), populations of Pseudomonas spp. and Enterobacteriaceae on c,hicken breasts were determined before, after treatment and after storage for 1, 3, 7, 10, and 14 days at 4°C. Surviving aerobic organisms were isolated and identified from chicken breasts treated with lauricidin, lactic and oxalic acids. Dipping chicken breasts in solutions of lauricidin, lactic and oxalic acids caused significant (P~0.05) reduction in APC and also retarded microbial growth throughout the 14 d storage period. APC on chicken samples treated with 0.5 to 2.0% lauricidin, lactic acid and oxalic acid solutions were significantly (P ~ 0.05) reduced by 0.92 - 1.2, 0.53-2.36 and 1.38-2.76 log CFUlg, respectively. Initial Pseudomonas counts on samples treated with 0.5 to 2.0% lauricidin and lactic acid were in the range of 0.79 - 1.77 and 0.39 - 1.82 log CFU/g, respectively, which were significantly (P ~ 0.05) lower compared to fresh samples, and growth of Pseudomonas spp. was limited throughout the storage period. In chicken breasts treated with 0.5 to 2.0% lauricidin and lactic acid, Enterobacteriaceae counts decreased by 0.14-1.14 and 0.59-2.18 log CFU/g, respectively. Less than log 2 CFU/g Enterobacteriaceae and Pseudomonas counts were observed on samples treated with 1.0 - 2.0% oxalic acid for 10 to 30 min. Enterobacter cloacae, Pseudomonas lundensis and Kocuria rhizophila were the predominant aerobic organisms isolated from chicken breasts treated with 0.5 to 2.0% lauricidin, lactic acid and oxalic acid, respectively. Lauricidin, lactic and oxalic acids were also evaluated for their effects on growth and survival of Listeria monocytogenes (L55), Salmonella Enteritidis (8552) and Escherichia coli 0157:H7 (EI9) inoculated onto raw chicken breasts. In chicken breasts treated with 0.5 to 2.0% lauricidin, initial counts of L. monocytogenes, S. Enteritidis and E. coli 0157:H7 were significantly (P ~ 0.05) reduced by 2.90, 1.31 and 2.27 log CFU/g, respectively. L. monocytogenes, S. Enteritidis and E. coli 0157:H7 counts on samples treated with lactic acid were significantly (P ~ 0.05) reduced by 1.97, 1.71 and 2.59 log CFU/g, respectively. Initial counts of L. monocytogenes, S. Enteritidis and E. coli 0157:H7 in chicken samples treated with oxalic acid were significantly (P ~ 0.05) reduced by 2.87, 2.02 and 4.12 log CFU/g, respectively. Dipping of chicken breasts in higher concentrations of solutions of lauricidin, lactic and oxalic acids and longer dipping time gave additional benefit. The colour and pH of chicken breasts dipped in solutions of lauricidin, lactic acid and oxalic acid were also evaluated. Sensory attributes of chicken breasts dipped in oxalic acid were determined. Oxalic acid residues in chicken breasts treated with oxalic acid were also determined. Dipping of chicken breasts in 0.5 to 2.0% lauricidin, lactic acid and oxalic acid caused significant (P ~ 0.05) decreased in pH, however, the decrease in pH was more pronounced in samples dipped in oxalic acid. Dipping chicken breasts in 0.5 to 2.0% lauricidin, lactic acid and oxalic acids caused slight darkening, as reflected by the increase in Hunter L values. Lauricidin caused a slight decrease in Hunter a value (decreased redness), and an increase in Hunter b value (increase in yellowness). Lactic acid also caused an increase in Hunter a values (increased redness) and Hunter b values (increased yellowness). Oxalic acid gave a more bleached chicken breasts compared to lauricidin and lactic acid. Higher concentrations of oxalic acid and longer dipping time caused more bleaching of the chicken breasts compared to lower concentrations and shorter dipping time. The maximum residue of oxalic acid in unwashed chicken breasts was 36 mg/IOOg (in chicken samples dipped in 2% oxalic acid for 30 min). Oxalic acid residue significantly (P ~ 0.05) decreased by more than 50% when the chicken breasts were washed and subsequently cooked. The maximum residue of oxalic acid in roasted chicken breast was 2 mg/100g. Results showed that lauricidin, lactic and oxalic acids have the potential to be used as a sanitizer in chicken carcasses during processing. Sensory evaluation of chicken breasts treated with oxalic acid demonstrated that, even though instrumental measurements may indicate deterioration in appearance, cooked chicken breasts were acceptable to consumers.